Filtration effectiveness of HVAC systems at near‐roadway schools. (25th January 2013) - McCarthy, M. C.; Ludwig, J. F.; Brown, S. G.; Vaughn, D. L.; Roberts, P. T.
Abstract Concern for the exposure of children attending schools located near busy roadways to toxic, traffic‐related air pollutants has raised questions regarding the environmental benefits of advanced heating, ventilation, and air‐conditioning (HVAC) filtration systems for near‐road pollution. Levels of black carbon and gaseous pollutants were measured at three indoor classroom sites and at seven outdoor monitoring sites at Las Vegas schools. Initial HVAC filtration systems effected a 31–66% reduction in black carbon particle concentrations inside three schools compared with ambient air concentrations. After improved filtration systems were installed, black carbon particle concentrations were reduced by 74–97% inside three classrooms relative to ambient air concentrations. Average black carbon particle concentrations inside the schools with improved filtration systems were lower than typical ambient Las Vegas concentrations by 49–96%. Gaseous pollutants were higher indoors than outdoors. The higher indoor concentrations most likely originated at least partially from indoor sources, which were not targeted as part of this intervention.